First time around: Local conditions and multi-dimensional integration of refugees - Cevat Giray Aksoy; Panu Poutvaara; Felicitas Schikora (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We study the causal effect of local unemployment and attitudes towards immigrants at the time of arrival on refugees' multi-dimensional integration outcomes. We leverage a centralized allocation policy in Germany where refugees were exogenously assigned to live in specific counties. Both high unemployment and negative attitudes hurt refugees' economic and social integration, independently of each other. A onestandard-deviation increase in unemployment or in negative sentiment index based on geo-coded tweets in 2014 predicts five percentage points lower probability of refugees being employed in 2016 to 2018. The estimated negative effects of far-right vote share are qualitatively similar.
Keywords: F22; J15; J24; 330; International migration; refugees; integration; allocation policy; far-right voting; negative sentiment